‘A Modern Liberation’. Belgium and the Start of the American Century, 1944-1946 - Peter Schrijvers (European Journal of American Studies)
The historiography of the liberation of Belgium traditionally focuses on military operations and the first enthusiastic encounters with Allied troops in September 1944. In reality, however, Allied forces remained stationed on Belgian soil until late in 1945, causing relations to be much more complex than is generally remembered. This paper examines the American presence in Belgium, both in terms of waves of admiration and currents of discontent, and concludes that, despite their mixed reception, American troops more than any others came to represent a ‘modern’ liberation creating rising expectations